Internal Control Disclosure and Financial Reporting Quality : Evidence from Banking Sector in Indonesia - Arisandi, Ariza; Islami, Henis Ayu; Soeprajitno, Raden Roro Widya Ningtyas (E-Jurnal Akuntansi; Vol 32 No 2 (2022)DO - 10.24843/EJA.2022.v32.i02.p15, 2022)
The purpose of this study is to examine the influence of Internal Control Disclosure Index (ICDI) and discretionary accruals (as a proxy for financial reporting quality). This study uses a data collection of Indonesian Stock Exchange listed banking sector companies’ financial statement and annual reports in 2016-2019. Sample was chosen using purposive sampling method. The analysis method used in this study is using STATA. The results of this study indicate that internal control disclosure there is significantly related to financial reporting quality. This research contributes empirically to the development of the literature as well as practically becomes a consideration for relevant management in making corporate decisions regarding the disclosure of their internal controls. Keywords: Internal Control Disclosure; Financial Reporting Quality; Banking.